Case Report: Bevacizumab-induced renal-limited TMA and FSGS-like lesions in a kidney transplant recipient - Jian, Xingxing; Liu, Ge; Yu, Shuangyan; Sheng, Jie (Frontiers in Oncology, 2025)
Bevacizumab, an anti-VEGF agent commonly employed in cancer therapy, can induce renal vascular endothelial and podocyte damage by inhibiting VEGF, leading to renal disease. We present a case of nephrotic syndrome and renal insufficiency arising from small intestinal mucinous adenocarcinoma 17 years post-renal transplantation, treated with bevacizumab and sindilizumab. Renal biopsy confirmed renal-limited thrombotic microangiopathy (TMA) with FSGS-like lesions in the transplanted kidney, attributed to bevacizumab. Upon discontinuation of the antitumor drugs and initiation of treatment with telmisartan, fenoldopam, and ambrisentan, proteinuria markedly decreased and eGFR improved. No tumor recurrence was observed over a follow-up period exceeding six months.